2023
DOI: 10.19101/ijatee.2023.10101498
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on endpoint vulnerabilities of blockchain applications

Abstract: In networking, an endpoint is a device or location that is used to access a network. It includes computers, laptops, servers, smartphones, and other devices connected to the network [1]. Endpoints are typically used to access network resources and services, such as the internet or internal network resources. Endpoints are often the target of attackers, as they can be used to gain access to a network and its resources [2]. So, endpoint protection is exigency. The experts suggest many standards policies, practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Finally, around 25 papers (Table 2) were found that described the taxonomy of blockchain or blockchain vulnerabilities or blockchain components or applications. However, as discussed in 'Limitations' section, there was lack of literature, so, to add more details and clarity another 22 studies were considered from our published work, 82 particularly review or survey studies related to blockchain endpoint vulnerability/attack classification. Table 3 Singh et al 20…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, around 25 papers (Table 2) were found that described the taxonomy of blockchain or blockchain vulnerabilities or blockchain components or applications. However, as discussed in 'Limitations' section, there was lack of literature, so, to add more details and clarity another 22 studies were considered from our published work, 82 particularly review or survey studies related to blockchain endpoint vulnerability/attack classification. Table 3 Singh et al 20…”
Section: Methodsmentioning
confidence: 99%
“…Sigurdsson et al In a nutshell, the studies collected through the selection procedure did not appear sufficient to constitute substantial literature; so, further papers from 82 were included to address the publication drought on the endpoint vulnerabilities taxonomy.…”
Section: Vulnerabilities and Security Breaches In Cryptocurrencies 2020mentioning
confidence: 99%